The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1515/bot-2023-0053
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature stress induces bacteria-specific adverse and reversible effects on Ulva (Chlorophyta) growth and its chemosphere in a reductionist model system

Imen Hmani,
Fatemeh Ghaderiardakani,
Leila Ktari
et al.

Abstract: Axenic cultures of the green seaweed Ulva mutabilis were inoculated with bacteria providing essential algal growth and morphogenesis-promoting factors (AGMPFs) and were exposed to temperature shifts from 18 °C to 30 °C. The temperature-dependent effect of bacteria on longitudinal algal growth and the molecular composition of the chemosphere in the algal culture medium was explored. The reductionist tripartite model system of U. mutabilis, Roseovarius sp. MS2, and Maribacter sp. MS6 was applied as a reference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Microbiome analysis was accompanied by functional examinations to investigate growth and morphogenesis-promoting traits within the microbiome (Hmani et al 2023). For this, bacteria were isolated from the surface of the algal samples using sterile swabs.…”
Section: Identification Of Bacteria That Release Essential Agmpfs Usi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiome analysis was accompanied by functional examinations to investigate growth and morphogenesis-promoting traits within the microbiome (Hmani et al 2023). For this, bacteria were isolated from the surface of the algal samples using sterile swabs.…”
Section: Identification Of Bacteria That Release Essential Agmpfs Usi...mentioning
confidence: 99%
“…However, these functions may be broadly distributed across various taxonomic groups (Burke et al 2011). In addition, functional characteristics within the same microbiome can also change in a changing environment (Hmani et al 2023). By employing mass spectrometry profiling and imaging techniques, specific metabolic markers have been introduced to visualize the distribution of bacteria (the producers of metabolic markers) on the surface of Ulva spp.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms able to flourish in association with macroalgae living in such distinctive and challenging ecological niches are expected to possess unique adaptive mechanisms and diversity. Recently, studies using Chlorophyta Ulva species have shown that the macroalgae‐associated bacterial community, including Actinomycetota, can have beneficial and adverse effects on host growth and development depending on environmental stress conditions (Ghaderiardakani et al, 2017; Hmani et al, 2023). In the single study harnessing exclusively the diversity and bioactive potential of the Actinomycetota culturable community associated with kelp from the northern Portuguese shore, a rich reservoir of taxonomically diverse strains producing antimicrobial and anticancer metabolites was uncovered (Girão et al, 2019).…”
Section: Introductionmentioning
confidence: 99%